KONSTITUSIONALITAS PROSES PEMBENTUKAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 2 TAHUN 2022 TENTANG CIPTA KERJA DAN HUBUNGANNYA DENGAN MEKANISME CHECK AND BALANCES - Wuran, Perseverando Elkelvin; Stefanus, Kotan Y; Tupen, Rafael R (Petitum Law Journal, 2024)
Article 22 paragraph (1) of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) regulates the existence of Government Regulations in Lieu of Law. This provision gives the President the authority to enact a of Government Regulations in Lieu of Law in a compelling emergency situation. This research is a normative legal research. Normative legal research is based on the study of legal issues that encompass research on legal principles, legal systematics, levels of vertical and horizontal synchronizations, legal comparisons, and legal history. The results of this research show that: (1) The process of establishing the Job Creation of Government Regulations in Lieu of Law is not in accordance with the regulations contained in Article 22 paragraph (2) of the NRI Constitution, because the discussion of the approval of the Job Creation of Government Regulations in Lieu of Law which was postponed and could not be carried out during the first session after the issuance of the of Government Regulations in Lieu of Law is evidence of a denial of the meaning of the matter of urgency. which gives rise to urgency (2) The presence of the Job Creation of Government Regulations in Lieu of Law as a legal institution which so far has only created dynamics in power relations between the DPR and the President also demands the role and function of the Constitutional Court as part of checks and balances in controlling and maintaining the balance between powers, so that the measure of the President's subjectivity in determining the terms of "urgency" which is coercive" before enacting the of Government Regulations in Lieu of Law, apart from being politically supervised by the DPR, it can also be legally controlled by the MK.